Bromatological composition and ruminal degradability of Xaraés palisade grass under grazing in integrated systems - Silva, Francyelle Ruana Faria da; Salman, Ana Karina Dias; Cruz, Pedro Gomes da; Porto, Marlos Oliveira; Cavali, Jucilene; Ferreira, Elvino; Souza , Elaine Coimbra de; Carvalho, Giovanna Araújo de (Acta Scientiarum. Animal Sciences, 2021)
To evaluate the bromatological composition and ruminal degradability of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) of Xaraés palisade grass (Urochloa brizantha ‘Xaraes’ syn Brachiaria brizantha) under grazing in integrated crop, livestock (ICL), and forest (ICLF) systems, we conducted an in situ degradability trial in randomized blocks with three non-lactating 3/4 Gyr × 1/4 Holstein cows, provided with ruminal cannula. The management of Xaraés palisade grass was similar in both systems, differing only regarding shading in the ICLF system provided by eucalyptus trees (average 65% crown cover). Grass samples were incubated for 0, 3, 6, 9, 12, 24, 36, 48, 72, and 96 hours. Considering the passage rate 2% h-1, the Xaraés palisade grass of ICL system had greater NDF effective degradability in relation to ICLF (46.38% vs 44.98%). However, the palisade grass CP potential degradability was greater in the ICLF than in the ICL system (68.92% vs. 65.40%). The presence of trees in the pasture has effect on nutritional traits of the Xaraés palisade grass, increasing its protein content and degradability and reducing its fiber degradability.